Peningkatan Pengetahuan Orangtua tentang pentingnya Nutrisi, Imunisasi yang optimal dalam 1000 Hari Pertama Kehidupan - Fairuza, Firda; Sari, Meiriani; Ningrum, Nathalia; Setiati, Dita; Ferdi Fadilah, Tubagus; Aziza, Nia Nurul (Fakultas Kedokteran Gigi, Universitas Trisakti bekerjasama dengan Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Trisakti, 2024)
Community service activities were carried out through education on the importance of the First 1000 Days of Life, vaccinations in children, and Complementary Foods in improving children's health and nutritional status in the Ciangsana Primary Healthcare working area. The target of this activities are mothers of toddlers who come to the integrated healthcare center (Posyandu) in the Ciangsana Primary Healthcare working area in Bogor, located at the Nagrak Trisakti Campus. Nutrition and health problems, especially in toddlers, can be prevented by educational activities provided through Posyandu activities. The solution carried out in community service activities was to provide education on the First 1000 Days of Life to parents of toddlers, precisely mothers who come to visit Posyandu. The purpose of the service activity was to increase the knowledge of parents of toddlers about the importance of the First 1000 Days of Life and nutrition in toddlers to optimize the nutritional and health status of toddlers so that mothers can provide appropriate care for the process of growth and development of children to prevent health and nutrition problems in toddlers. The benefit of this activity was that parents, especially mothers of toddlers, know the importance of the First 1000 Days of Life to prevent nutritional problems in toddlers and improve their health and nutritional status.